Avaliação dos efeitos do Ácido Ascórbico, Curcumina e Resveratrol em cultura de células-tronco mesenquimais - Salazar, Rhana Evangelista (2023)
Antioxidant substances have often been used for therapeutic purposes, as they operate in cells as anti-aging substances, and help maintain the cell's redox balance, aiding in cell homeostasis and ensuring cell integrity. Ascorbic acid, curcumin and resveratrol are found in easily accessible natural sources and are widely known for their antioxidant potential. These substances can be used as adjuvants in disease treatments. In the search for substances with biotherapeutic potential, in vitro experiments with mesenchymal stem cells (MSC) stood out, which can show powerful or toxic effects at the cellular level. A disease of genetic etiology that predisposes to fractures and bone deformities is Osteogenesis Imperfecta (OI). In most cases, patients with OI have failures in the synthesis of type I collagen, an important protein component of bone tissue. Thus, this study sought to assess whether in vitro treatment of MSC with ascorbic acid, curcumin and resveratrol affected cell viability in in vitro experiments of patients with OI and controls. By means of the MTT method, which evaluates cell viability, transient MSC of adipose tissue from patients with OI and controls were treated with ascorbic acid (10, 25, 50, 100 and 200μg/mL), curcumin (0.05, 0 .01, 0.3, 0.5 and 0.8μg/mL) and resveratrol (6.25, 12.5, 25, 50 and 100μM/mL) and analyzed after 24, 48 and 72 hours. The results were statistically analyzed by the one-way ANOVA test, followed by the Tukey comparison test. In general, the results suggest that ascorbic acid, curcumin and resveratrol positively interfere with MSC cell viability in concentrated concentrations. The results support the development of research on these substances as potentially biotherapeutic in the adjuvant treatment of OI.